WorldFish Accelerator Partners’ Story, CSA Bundle two focusing on Integrated Aquaculture Agriculture - Chileya, Agness; Mudege, Netsayi (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Scaling climate smart aquaculture. WorldFish sought to improve access to fish, enhance nutrition, and create job opportunities for women and youth in Zambia's urban, peri-urban, and rural areas in Northern and Luapula provinces by promoting models to improve access to aquaculture inputs, output markets, extension, and climate-smart information systems. The video highlights the benefits that these interventions have had on local fish farmers.